South Africa's energy crisis : reconciling economic growth with environmental protection - Bagley, Constance E., (SAGE knowledge. Cases., 2016)
In October 2007, chaos ensued when traffic lights in South Africa's famed commercial center, Johannesburg, failed without warning. That the cause was a power line fault only underscored how strained South Africa's energy system had become. Severe blackouts continued until the summer of 2008, creating widespread socioeconomic damage and stifling the country's growth. This case study discusses this topic.